Effect of educational brochure compared with video on disease-related knowledge in patients with juvenile idiopathic arthritis: A randomized controlled trial - Sunthornsup, Waraporn; Vilaiyuk, Soamarat; Soponkanaporn, Sirisucha (Frontiers in Pediatrics, 2022)
Introduction: Patient education plays an important role in the management of chronic diseases such as juvenile idiopathic arthritis (JIA). This study compared the effectiveness of a brochure and a video regarding JIA-related knowledge immediately after the intervention, and at 4 weeks post-intervention. Methods: A prospective randomized controlled trial was conducted. Patients with JIA and their parents were randomized to receive education from either a brochure (n = 50) or a video (n = 50) at the clinic. Participants answered questionnaires about disease-specific knowledge before the intervention (T0), immediately after the intervention (T1), and at follow-up 4 weeks later (T2). The questionnaire comprised 15 multiple-choice questions. Final scores ranged from 0 to 15, and were scaled from 0% to 100% to calculate the percentage of knowledge scores. Ninety participants completed the questionnaire at T2 (42 in the brochure and 48 in the video group). Results: The mean percentage of knowledge scores at T0 was not significantly different between the brochure group and the video group. At T1, the mean percentage of knowledge scores was significantly higher in the video group compared with the brochure group (86.7 ± 12.9% vs. 76.0 ± 21.4%, p = 0.003). Among parents with an educational level below secondary school, the mean percentage of knowledge scores at T1 was significantly higher in the video group compared with the brochure group (83.5 ± 14.4% vs. 69.1 ± 23.2%, p = 0.006). Participants in both groups had significantly higher mean percentage of knowledge scores at T2 compared with T0 (72.7 ± 20.3% vs. 51.1 ± 24.7%, p < 0.001 in the brochure group and 78.3 ± 15.7% vs. 56.1 ± 21.9%, p < 0.001 in the video group). There was no significant difference in the mean percentage of total score change between T2 and T1 between the brochure and video groups (−4.7 ± 13.3% vs. −8.5 ± 11.0%, p = 0.152). Conclusion: The video was more effective for improving disease-related knowledge immediately post-intervention, particularly in participants with limited education. Although both educational tools had lasting effects on knowledge, the retention rate declined at 4 weeks after both interventions.